The role of Mathematics Education in Developing Critical Thingking Skill in the Industrial Era 5.0 - Duma, Sonny Yalti; Muslimin; Modjo, Ardiyanto Saleh; Walid, Abul (PT. Anagata Sembagi Education, 2024)
This study explores the role of mathematics education in developing critical thinking skills in students within the context of Industry 5.0. As industries evolve and integrate human creativity with advanced technologies, the demand for critical thinking and problem-solving abilities has become more pronounced. Mathematics education, with its focus on logic, analysis, and problem-solving, is uniquely positioned to nurture these skills. The research employs a quantitative survey approach with a descriptive correlational design, analyzing the relationship between mathematics instruction and the development of critical thinking among high school and university students. A total of 150 respondents participated, all of whom had been exposed to problem-solving-based mathematics teaching methods. The study investigates the effectiveness of these methods in enhancing students’ critical thinking abilities and their relevance to meeting the challenges of Industry 5.0. Findings suggest a significant positive correlation between problem-solving mathematics education and the improvement of critical thinking skills. This research highlights the importance of integrating critical thinking into mathematics curricula to better prepare students for the digital and technological demands of the modern workforce.